Synergetic disintegration of waste activated sludge: improvement of the anaerobic digestion and hygienization of sludge - Grübel, Klaudiusz; Wacławek, Stanisław; Machnicka, Alicja; Nowicka, Ewelina (Journal of environmental science and health. Part A, Toxic/hazardous substances & environmental engineering, 2018)
The main aim of this study was to investigate the impact of a hybrid disintegration process with the use of alkalization and freezing by dry ice on waste activated sludge (WAS) and on the course of the process of mesophilic methane fermentation. In order to achieve the mentioned goal, various analytical techniques were used for assessment of the sludge disintegration and its influence on the further biogas production. As a result of the investigation, it was found that the chemical-thermal process of destruction of WAS results in an increased concentration of organic compounds in the supernatant (expressed as a change in the value of the soluble chemical oxygen demand - SCOD). The use of disintegrated WAS and feeding of the material into the fermentation digester influences, depending on its proportion by volume, the production of biogas and the biogas yield (higher biogas production by ca. 39% in comparison to blank sample was achieved with the appropriately disintegrated sludge). The hybrid process is simple and easy to implement in the full technical scale and does not influence or change the pH value of the sludge feed into the fermentation chambers (the dry ice neutralizes the high pH of the sludge). Additionally, it was determined that the herein developed process, can improve hygienization of the digested sludge.
Keywords: bioreaktory; anaerobióza; Hydrolysis; Waste activated sludge; Sewage; Methane; Anaerobiosis; Water Purification; methan; Sanitation; Biofuels; Biological Oxygen Demand Analysis; Bioreactors; biopaliva; anaerobic stabilization; čištění vody; odpadní vody; alkalization; koncentrace vodíkových iontů; měření biologické spotřeby kyslíku; hygienization; hydrolýza; freezing; odpad tekutý - odstraňování; Waste Disposal, Fluid; sanitace; Hydrogen-Ion Concentration